Strengthening Community-Based Disaster Literacy and Psychosocial Support Through Community Learning Centers (TBM): A Participatory Approach in Post-Disaster Areas in Kampung Darussalam, Langkat Regency - Mahfuzi Irwan; Artha Mahindra Diputera; Asiah Asiah; Dimas Istiqo Anggoro; Serasi Zendrato; Fira Aprilia (Program Studi Pengembangan Masyarakat Islam, 2026)
This study demonstrates the effectiveness of a participatory, TBM-based approach in strengthening disaster literacy and psychosocial well-being in post-disaster communities. The findings show a significant improvement in disaster literacy, with most participants progressing from low baseline understanding to moderate and high levels, and around 75% able to identify risks, explain evacuation procedures, and demonstrate basic preparedness. Community participation also increased substantially, particularly among children and youth, indicating that interactive and contextual learning approaches enhance engagement and learning outcomes. Beyond cognitive gains, the study reveals important psychosocial improvements, including reduced anxiety, increased emotional stability, and stronger social interaction. The integration of trauma healing and community-based counseling within learning activities proved effective in supporting emotional recovery and rebuilding social cohesion. These findings confirm that combining disaster literacy and psychosocial support within a participatory framework produces more comprehensive outcomes than fragmented interventions. The study contributes by offering a contextual, integrative, and sustainable model that strengthens both cognitive and socio-emotional capacities. It also highlights the evolving role of TBM as a community resilience hub, demonstrating its strategic potential in supporting post-disaster recovery and long-term community empowerment.